Ocorrência de polimorfismo em matérias-primas de espironolactona e avaliação da influência na qualidade físico-química de comprimidos - Oliveira, Renata Cunha De Resende (2016)
Spironolactone (SPR) is an active pharmaceutical ingredient (API), with steroidal chemical structure and diuretic activity, administered for arterial hypertension treatment, and also as antiandrogen agent. The drug shows incomplete gastrointestinal absorption due to its poor aqueous solubility that can difficult the drug release. The use of different solvents and crystallization processes for the synthesis of an API are factors that lead to formation of polymorphs. In Brazil, APIs have been purchased from different manufacturers, including different synthetic routes. Therefore, the physicochemical characterization and identification of the crystal structure of an API are important points to ensure its quality. Different crystal structures of a drug can lead to ineffective or toxic plasma concentrations, if different aqueous solubility were determined. In this study, SPR polymorphs in five batches of APIs from different manufacturers were characterized using powder X-ray diffraction, infrared spectroscopy, thermal analysis, and equilibrium solubility measurements. Tablets were manufactured using different APIs to assess the effect of drug polymorphism on their dissolution profiles. The APIs were identified as SPR-L1, L2, L3, L4 and L5; the standard as SPR-pd 2 ° NCQ, the reference drug product as SPR-R, and the batches of the manufactured tablets are denominated as batch A (SPR-L1) and batch B (SPR-L2). The results indicated that the APIs SPR-L2, L3, L4, L5 and standard SPR-pd 2 ° NCQ were characterized as pure form II although SPR-L1 contains both forms I and II. The equilibrium solubility measurements demonstrated that SPR-L1 solubility is higher than the SPR- L2 solubility in all aqueous media (p <0.01 using Student test). When the dissolution profiles of batches A and B were compared, the calculated value for F2 was 19.00, demonstrating that the dissolution of the manufactured tablets are not equivalent. Therefore, the presence of low amounts of polymorph I, a more soluble form, increases the dissolution rate of the drug. The increase in the dissolution rate could enhance the therapeutic effects of SPR due to changes in drug plasma concentrations, and cause hyperkalemia, leading to the appearance of undesirable side effects. Marketed SPR tablets in Brazil were also evaluated and formulation showed an important role in dissolution rate of the drug, leading to lack of pharmaceutical equivalence in these drug products.